Anonymous
Anonymous asked in Science & MathematicsMathematics · 2 years ago

How to solve this series : 7 + 3 - 1 + (3/4) - (9/16) + (27/64) - ... ? The answer is 66/7 but I don't know how to solve it.?

4 Answers

Relevance
  • sepia
    Lv 7
    2 years ago

    [7 + 3 - 1] + [(3/4) - (9/16) + (27/64) - ... ]

    = 9 + (3/7)

    = 66/7

  • 2 years ago

    You don't "solve" a series, but you can sum the series,

    i.e., find out its total value.

    I guess the series is meant to go on with alternating signs, and each term being (-3/4) times the previous term (even though this is not true of the first few terms.

    Let's look at it as the sum of three distinct series:

    (a) 7 + 3

    (b) - 1 - (9/16) - (81/256) - (729/4096) - etc.

    (c) (3/4) + (27/64) + (243/1024) + etc.

    The sum of (a) is 10.

    The sum of (c) is (3/4)/[1 - (9/16)] = (3/4)/(7/16) = 12/7.

    The sum of (b) is -(4/3) times the sum of (c), so it's -16/7).

    The sum of all three is 10 + 12/7 - 16/7 = 10 - 4/7 = 70/7 - 4/7 = 66/7.

  • Mike G
    Lv 7
    2 years ago

    (3/4) - (9/16) + (27/64) - ...

    S_∞ = (3/4)/[1+3/4] = 3/7

    3/7 + 9 = 3/7 + 63/7

    = 66/7

  • alex
    Lv 7
    2 years ago

    (3/4) - (9/16) + (27/64) - ... = (3/4)/(1-(-3/4)) = 3/7

    hence 7 + 3 - 1 + (3/4) - (9/16) + (27/64) - ... = ...

Still have questions? Get your answers by asking now.